Treatment of STING-associated vasculopathy with onset in infancy in patients carrying a novel mutation in the TMEM173 gene with the JAK3-inhibitor tofacitinib - Pervin Elvan Tokgun,; Nedim Karagenc,; Uğur Karasu,; Onur Tokgun,; Samet Turel,; Aydın Demiray,; Hakan Akca,; Selçuk Yüksel, (Archives of Rheumatology, 2023)
Objectives: This study aimed to reveal the genetic background of patients in the two-generation family suffering from rheumatoid arthritis, psoriatic arthropathy pain, scratches, and bruises. Patients and methods: A clinical exome sequencing analysis was performed in 10 individuals in the same family using the Sophia Genetics clinical exome solution kit. Results: A novel V194L mutation in the TMEM173 gene was identified in three members of the family. Two of the family members were treated with the JAK3 inhibitor tofacitinib and recovered completely one month after the treatment. Conclusion: The V194L mutation was reported for the first time in this study, and a positive response was achieved with tofacitinib.